A Deconstruction of the Meaning of Character Values in Chairul Harun’s Novel “Warisan” - Zulfardi D.; Hendry Sugara (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study examines how character education values are constructed and challenged in Chairul Harun’s novel Warisan. While traditional literary analyses often treat cultural and moral frameworks as fixed guidelines, this research explores how such values are actively contested and renegotiated within the narrative. Using the complete text of Warisan as the primary data source, the analysis follows a hermeneutic-deconstructive four-stage process—identifying explicit moral themes, mapping narrative tensions, deconstructing binary oppositions, and synthesizing cultural negotiations—to examine how this Minangkabau regional novel uniquely portrays inheritance and identity as fluid rather than fixed. The findings reveal two main points: first, culturally respected values are frequently used to justify personal or group interests rather than reflecting genuine communal ethics; second, the narrative emphasizes an ongoing negotiation between individual agency and cultural expectations, with characters ultimately prioritizing moral and spiritual legacies over material wealth. By demonstrating that ethical meaning in literature is dynamic rather than absolute, the study challenges traditional, lesson-based approaches to character education. It recommends that literary instruction should focus on developing students’ critical literacy and ethical independence. Ultimately, this research contributes to Indonesian literary scholarship by providing a clear analytical framework that connects cultural interpretation with critical reading, while offering actionable insights for teaching character education through regional fiction